2011
DOI: 10.1016/j.nlm.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids are required for extinction of predator stress-induced hyperarousal

Abstract: Extinction of fearful behavior induced by severe stress was studied using predator stress. Predator stress involves a ten minute unprotected exposure of a rodent to a cat which induces long-lasting changes in anxiety-like behaviours and hyperarousal (increased acoustic startle response) (Adamec & Shallow, 1993; Adamec et al., 200 I;Cohen et al., 2004). In the present set of experiments, three questions were addressed using predator stressed mice. First, can predator stress-induced fear memories be extinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 104 publications
3
16
0
Order By: Relevance
“…We report that predator odor produced hyperarousal 24–48 hrs post odor-exposure, in agreement with previous reports that predator stress produces lasting increases in startle reactivity in rats (Adamec et al, 2010) and mice (Clay et al, 2011). Other modalities of stress (e.g., footshock or restraint) also produce increases in arousal in rodents as measured by the acoustic startle test (Chester et al, 2008; Jiang et al, 2011; Rasmussen et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…We report that predator odor produced hyperarousal 24–48 hrs post odor-exposure, in agreement with previous reports that predator stress produces lasting increases in startle reactivity in rats (Adamec et al, 2010) and mice (Clay et al, 2011). Other modalities of stress (e.g., footshock or restraint) also produce increases in arousal in rodents as measured by the acoustic startle test (Chester et al, 2008; Jiang et al, 2011; Rasmussen et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have also demonstrated the role of the glucocorticoid system in fear memory extinction (Barrett and GonzalezLima, 2004;Blundell et al, 2011;Clay et al, 2011;Yang et al, 2006Yang et al, , 2007 (see Table 2). For instance, Barrett and Gonzales-Lima showed that the release of corticosterone is fundamental for the extinction of conditioned fear, since extinction can be impaired by inhibition of corticosterone synthesis with metyrapone (Barrett and Gonzalez-Lima, 2004) or by adrenalectomy (Bohus et al, 1982).…”
Section: Enhancing Fear Memory Extinction: Endocannabinoids and Glucomentioning
confidence: 99%
“…The answer is still not obvious, but here we propose a tentative model. We have seen that both eCB (Chhatwal et al, 2005;Marsicano et al, 2002) and glucocorticoids Clay et al, 2011;Yang et al, 2006Yang et al, , 2007 are essential to the extinction of aversive memories. Additionally, we have also seen that glucocorticoids can increase eCB levels (Di et al, 2003;Hill et al, 2005Hill et al, , 2011Patel et al, 2005).…”
Section: A Putative Mechanism For Fear Memory Extinction Involving Thmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the data suggesting that endocannabinoids [14][15] and glucocorticoids [91][92] mediate the extinction of aversive memories and that glucocorticoids can increase endocannabinoids levels [93][94][95], they suggested that endocannabinoids are recruited by glucocorticoids in the process of extinction of aversive memories. As endocannabinoids are released in the basolateral amygdala during fear extinction [15], and glucocorticoids can trigger endocannabinoids release at this location, they hypothesized that an endocannabinoid-mediated feedback of the hypothalamic-pituitary-adrenal axis, which is dependent on glucocorticoid release, is an important component of the mechanism of fear memory extinction.…”
Section: A Possible Model For the Effects Of Win55212-2 On Memory Afmentioning
confidence: 99%